Nurse Caring and Mother Stress Level on Baby Hospitalization During the COVID-19 Pandemic - Endar Timiyatun; Sri Nur Hartiningsih; Sarjiyah; Eka Oktavianto (Caring: Indonesian Journal of Nursing Science, 2022)
Parents, mainly mothers, will be stressed when their children undergo hospitalization. Especially during the Covid-19 pandemic, the stress level goes higher. Nurse caring and nurse attitudes are treatments to lower mother stress levels. This research aims to see the correlation between nurse caring and mother stress levels on baby hospitalization during the Covid-19 pandemic. This research is observational and uses a cross-sectional design and accidental sampling technique. The samples are 95 mothers whose babies are being cared for in the neonatal intensive care unit at one of Yogyakarta's hospitals from December 2020 â€“ January 2021. The instrument is the Caring Assessment Toll (CAT) questionnaire and the Parental Stress Scale (PSS). The Chi-square test was used as the statistical test. The result showed that 50 people (52.6%) said nurse caring was good. Then, 86 people (90.5%) have low to mid-stress levels. Thirty-eight people (40%) are the ones who categorized nurse caring as a good which affects their low-stress level. The p-value is 0.000 (p-value < 0.05). It can be concluded that there is a correlation between nurse caring and a mother's stress level during baby hospitalization in a perinatology room. Hopefully, the perinatology room nurses should improve their care, especially during the pandemic. Â